Measuring patient and family perceptions of team processes and outcomes in healthcare teams: questionnaire development and psychometric evaluation - Kelley Kilpatrick; Éric Tchouaket; Lysane Paquette; Claudel Guillemette; Mira Jabbour; François Desmeules; Véronique Landry; Nicolas Fernandez (BMC Health Services Research, 2019)
Abstract Background There is a lack of validated instruments examining dimensions of team functioning from the perspective of patients and families consistent with a conceptual framework. The study aimed to develop and assess the psychometric properties of the Patient-Perceptions of Team Effectiveness (PTE) questionnaire. Methods A cross-sectional survey was undertaken in three studies. Data were collected from May–October 2016 for Study 1, April 2018-ongoing for Study 2, and October 2016 to June 2017 for Study 3. Online and paper versions of the self-administered questionnaire were available in English and in French. The initial questionnaire included 41 items. Study 1 included 320 respondents. Reliability was assessed using Cronbach alpha. Face validity (n = 250) was assessed using a structured questionnaire. Content validity was examined using subject matter experts and Spearman’s item-total correlations. Construct validity was examined using known group comparisons (i.e., clinical specialty, education, length of follow-up, reason of consultation). Content analysis was used for open-ended questions. Results The questionnaire took 10 to 15 min to complete. Positive assessments were noted for instructions, formatting, font size and logical ordering of questions. In Study 1, reliability indices for the PTE-Overall, Team Processes and Outcomes subscales ranged from 0.72 to 0.84. Item-total correlations ranged from 0.551 to 0.794 (p <  0.001). Differences were noted between clinical specialties, education, length of follow-up, reason of consultation, low and high functioning teams. No differences were noted between English and French language respondents. Psychometric properties were re-assessed in Study 2 and 3 after unclear questions were reworked. Reliability indices for the subscales ranged from 0.76 to 0.94 and differences remained significant between low and high functioning teams. Conclusion The final 43-item instrument is easy to administer to patients and families. The studies provide evidence of validity to support the propositions in the conceptual framework. The patient-level measures can be aggregated to the team, organizational or system level. The information can be used to assess healthcare team functioning in acute and primary care and determine the role patients and families are playing in teams. Further testing is needed with patients and families who are hospitalized or receiving care from teams in rural areas.